PERAN MADRASAH IBTIDAIYAH DALAM PENDIDIKAN KARAKTER - Komariyah, Siti; Purwanto (Program Studi PGMI Fakultas Tarbiyah Institut Agama Islam Nahdlatul Ulama Tuban, 2023)
Abstract The rise of cases of immoral acts occurred among students. Fights, harassment or bullying, even murder as normal and satisfaction for students. For this reason, Madrasah Ibtidaiyah has a role in early childhood character education. In this study aims to; 1. Methods of character education in Madrasah Ibtidaiyah, 2. Purpose of education in Madrasah Ibtidaiyah, 3. Principles of character education in Madrasah Ibtidaiyah, 4. Strategy for character education in Madrasah Ibtidaiyah. The method used is descriptive qualitative, namely a study that describes in general the curriculum and learning activities in Madrasah Ibtidaiyah. The research results show; 1. The character education method in primary schools is direct by using habituation methods, exemplary methods, advice methods, attention methods and indirectly by means of prohibition or prevention. 2. The purpose of character education in Madrasah Ibtidaiyah is to create students who are clean in spirit by getting closer to Allah SWT. 3. The principle of Character Education in Madrasah Ibtidaiyah is to create and improve student character by caring for society and oneself. 4. Character Education Strategy in Madrasas, namely implementing character values ​​in subjects and student behavior, both in the school environment and the home environment. Keywords: Role, Madrasah Ibtidaiyah, Character Education